PENGARUH MASA KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. TELEKOMUNIKASI INDONESIA (TELKOM) PERSERO BIMA - Febryatun Ardiani; Sri Ernawati (Jurnal Bina Bangsa Ekonomika, 2022)
This study aims to determine and influence the length of service and organizational commitment on employee performance at PT. Telecommunications Indonesia (TELKOM) Persero Bima. This type of research is associative research. The research instrument used in this study was a questionnaire with a likert scale. The population in this study was 35 employees. The sample technique used in this study was Accidental Sampling, where all populations were used as research samples. The data collection techniques used are observation, questionnaires/ questionnaires and literature studies. The data analysis techniques used are validity test, reloability test, multiple linear regression analysis, multiple colleration coefficient, determination test, T test and F test. The results showed that the length of service, commitment to oragnization had a significant effect partially and simultaneously on the performance of PT. Telecommunications Indonesia (TELKOM) Bima